The Relationship of Clinical and Laboratory Factors with Acute Isolated Vertigo and Cerebellar Infarction - Cihan Bedel; Mustafa Korkut (Indian Journal of Medical Specialities)
Introduction: The aim of the study was to investigate the relationship between acute cerebrovascular infarction and risk factors in the patients presented to the emergency department (ED) with isolated vertigo symptoms. Materials and Methods: Ninety patients presented with isolated acute vertigo attack and/or dizziness symptoms were retrospectively analyzed. The criteria for inclusion in the study were patients with ≥18 years of age and patients with acute vertigo and/or dizziness and ischemic infarction on diffusion-weighted magnetic resonance imaging or computed tomography. The exclusion criteria were patients with peripheral vertigo, dizziness associated with a systemic disease, and incomplete data. The patients were categorized into two groups as cerebellar and noncerebellar according to the infarct localization. Results: The mean age of the patients was 60.31 ± 15.18 years and 43 patients were male. Of the patients, 34 (37.8) had cerebellar infarction and 56 (62.2) had noncerebellar infarction. There was no statistically significant difference between the two groups except for hyperlipidemia (67.6% in the cerebellar group, 35.7% in the noncerebellar group; P = 0.005). The multivariate logistic regression analysis revealed that hyperlipidemia (odds ratio [OR] = 3.233; 95% confidence interval [CI] = 1.144–9.136; P = 0.027) and imbalance (OR = 4.064; 95% CI = 1.271–12.995; P = 0.018) were the strongest indicators of cerebellar infarction in the patients with isolated vertigo. Conclusion: While the presence of accompanying nausea and vomiting in the ED is indicative of noncerebellar infarction, the risk factors of hyperglycemia and/or hyperlipidemia are strong indicators for the diagnosis of acute cerebellar infarction in isolated vertigo patients.